2014
DOI: 10.5978/islsm.14-or-13
|View full text |Cite
|
Sign up to set email alerts
|

The use of sub-ablative Er:YAG laser irradiation in prevention of dental caries during orthodontic treatment

Abstract: Purpose: This « in-vitro » study had two specific aims: the first, to test using a universal testing machine whether sub-ablative Er:YAG laser irradiation prior to acid etching is effective in orthodontic bracket bonding and secondly using micro-hardness measurements and Scanning Electron Microscopy (SEM) observations to investigate the effectiveness of de-mineralization reduction in enamel treated with sub-ablative Er:YAG laser irradiation followed by fluoride varnish application. Materials and Methods: One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
1
14
0
9
Order By: Relevance
“…Also, it is reported that Pulsed CO 2 laser irradiation caused enamel surface fusion and inhibition of the subsurface caries-like lesions with 50% success rate [22]. Moreover, increased micro-hardness of enamel surface was detected by several studies after laser application [7, 23]. …”
Section: Materials and Methodologymentioning
confidence: 99%
“…Also, it is reported that Pulsed CO 2 laser irradiation caused enamel surface fusion and inhibition of the subsurface caries-like lesions with 50% success rate [22]. Moreover, increased micro-hardness of enamel surface was detected by several studies after laser application [7, 23]. …”
Section: Materials and Methodologymentioning
confidence: 99%
“…Some studies3,5,911 have pointed out increased retention of the resinous material to enamel irradiated with Er:YAG laser. However, further studies need to be conducted in order to prove the efficacy of erbium laser for increasing the bond strength of orthodontic adhesives, since these data are controversial in the literature 6,7…”
Section: Introductionmentioning
confidence: 99%
“…Os Lasers podem ser classificados em Laser de baixa intensidade e Laser de alta intensidade. O Laser de baixa intensidade, por meio das reações fotoquímicas, pode ser aplicado no diagnóstico e na prevenção da cárie dentária, na desinfecção de canais radiculares, no tratamento de bolsas periodontais e da periimplantite e no clareamento dental 12 . Eles são relativamente barato, de pequeno porte, fácil de transportar e têm múltiplas aplicações em várias áreas da Odontologia 10 .…”
unclassified
“…O Laser de alta intensidade, por sua vez, pode ser usado no tratamento de doenças malignas, na remoção de tecido cariado, no preparo de cavidades 12 , na cirurgia de tecidos moles e para melhorar a resistência da estrutura do dente à desmineralização 13 .…”
unclassified
See 1 more Smart Citation